2020
DOI: 10.1136/bmjopen-2019-034296
|View full text |Cite
|
Sign up to set email alerts
|

Use of healthcare services and assistive devices among centenarians: results of the cross-sectional, international 5-COOP study

Abstract: ObjectivesTo measure the use of healthcare services and assistive devices by centenarians in five countries.DesignCross-sectional study using a survey questionnaire.SettingCommunity-dwelling and institutionalised centenarians living in Japan, France, Switzerland, Sweden and Denmark.Participants1253 participants aged 100 or in their 100th year of life, of whom 1004 (80.1%) were female and 596 (47.6%) lived in institutions.Main outcome measuresRecent use of medical visits, nursing care at home, home-delivered me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In total, 25 studies (12%) provided 62 indicators on hearing aid access, detailed in table 2 and online supplemental appendix 7 16–40. Nearly all were based on primary (n=10, 40%) or secondary analyses (n=14, 56%) of cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 25 studies (12%) provided 62 indicators on hearing aid access, detailed in table 2 and online supplemental appendix 7 16–40. Nearly all were based on primary (n=10, 40%) or secondary analyses (n=14, 56%) of cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (7%) reported 42 access indicators for mobility APs, including prosthetics, motorised and manual wheelchairs. Characteristics are included in table 3 and all indicators in online supplemental appendix 8 17 22 25 27 30 40–49. Most mobility AP studies (n=11, 73%) were secondary analyses of national-level surveys/censuses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of this study globally may not be possible as there have been shown to be differences between the health status of U.S. centenarians and centenarians in other countries [ 19 , 20 ]. While this data is potentially informative, cross-national comparisons are difficult due to differences in health status, health systems, and policies.…”
Section: Discussionmentioning
confidence: 99%